Meningkatkan Hasil Belajar Peserta Didik Melalui Penggunaan Media Pembelajaran PETA Pada Mata Pelajar Ilmu Pengetahuan Sosial Di Kelas VII.A SMP Negeri 1 Cariu Kabupaten BogorTahun Pelajaran 2018/2019 - Nahnu (JURNAL KAJIAN ISLAM MODERN, 2021)
This research was conducted in class VII A of SMP Negeri 1 CariuBogor Regency by using map media in an effort to improve student learning outcomes. This research is a classroom action research (Classroom Action Research). The subjects of this study were students of class VII A of SMP Negeri 1 Cariu as many as 36 students. This research took place in 2 cycles, each cycle consisted of one meeting. Data collection techniques used observation, field notes, and documentation. The type of data collected is data on student learning outcomes. The data analysis technique used is the data analysis technique quantitative which consists of data reduction, data presentation and drawing conclusions. The criteria for success in this research are if 75% of the students in class VII A have a minimum grade of 70 according to the curriculum of SMP Negeri 1 Cariu. The results of the study can be concluded as follows: The use of map media can improve student learning outcomes. This is evidenced by the percentage of students who achieve the KKM value in the first cycle of 42% increasing to 84% in the second cycle. This means that the number of students who achieve the KKM score (70) has exceeded the set success criteria of 75%.